Developing a Mobile App for Learning English Vocabulary in an Open Distance Learning Context - Mpine Makoe (Athabasca University Press, 2018)
Academic success depends on the comprehension of a language, which is linked to vocabulary learning. Many distance students in South Africa find it difficult to comprehend learning in a language other than their mother tongue. Finding effective strategies for enhancing English vocabulary of university students amidst the spatial, temporal, and pedagogic distance associated with Open Distance Learning (ODL) practices remains a challenge. To address the need for enhancing vocabulary development, mobile application systems (apps) were explored as the best vehicle for the delivery of the vocabulary learning. Mobile learning technologies are ideal in the ODL context because they are flexible, accessible, available, and cater for a myriad of interaction activities. The purpose of the study is to design and implement a mobile-based application aimed at enhancing English vocabulary teaching and learning.  Using the Design-Based Research methodology, this study maps the steps taken to develop a vocabulary learning mobile app named VocUp; it describes the architecture, user interface, features of VocUp, and advocates for contextually-conscious and learning-driven app development.